Identification of dietary patterns of adolescents attending public schools - Lucinéia de Pinho; Marise Fagundes Silveira; Ana Cristina de Carvalho Botelho; Antônio Prates Caldeira (Brazilian Society of Pediatrics, 2014)
Objective: to identify the dietary patterns of adolescents attending public municipal schools in Northern Minas Gerais, Brazil, and to test the association between these patterns and socio-economic variables and nutritional status of the adolescents. Methods: this was an analytical, cross-sectional study with randomized sample of 474 adolescents of both genders, between 11 and 17 years of age, attending municipal public schools in the urban area of Montes Claros, MG, Brazil. The parents provided demographic and economic data. The nutritional status (body mass index - BMI) of the adolescents was determined at school, and their dietary habits were assessed though the administration of the Food Frequency Questionnaire for Adolescents (FFQA). Based on 26 categories extracted from FFQA, dietary patterns were determined using principal component analysis (PCA) and associated to anthropometric and socioeconomic factors using multiple regression analysis. Results: the three dietary patterns identified, "junk food," "healthy," and "traditional", explained 23.26%, 6.90%, and 5.24% of data variability, respectively. Adolescents with per capita family income exceeding half a minimum wage were more likely to consume the "junk food"pattern (OR = 1.66; 95% CI = 1.07-2.56), and overweight adolescents had lower chances of eating the "healthy" food pattern (OR = 0.56, 95% CI = 0.35-0.91). Conclusions: deviations from the "healthy" patterns were not associated to low income, but rather to bad eating habits in the studied population. Overweight adolescents did not adhere to the "healthy" dietary pattern, emphasizing the need for nutritional education among them.